Flavonoids of Tetrastigma hemsleyanum Diels et Gilg Against Acute Hepatic Injury by Blocking PI3K/AKT Signaling Pathway - Lingling Li; Lianghui Zhan; Xiaojun Wu; Xuechun Jiang; Jinbao Pu (Mediators of Inflammation)
Conclusion: The treatment of acute liver injury with THF is characterized by multicomponents and multitargets, and its mechanism may be related to the alleviation of the inflammatory response, reduction of apoptosis, and regulation of the PI3K/AKT signaling pathway.